Use of Acetone in Organic Synthesis and its Importance for Industrial Chemistry - Sunnatova Rukhshona Shuhrat kizi; Omanov Bekhruzjon Shukhrat ugli (Scientific Trends, 2024)
This study examines the methods of using acetone in organic synthesis and is dedicated to the study of its importance in industrial chemistry. Improving the production and utilization of acetone to reduce waste and increase efficiency is a key focus for future industry development. Acetone is one of the most tommon solvents in construction. Technical acetone production is carried out by vapor phase hydration of acetylene, purification and rectification of acetone on ZnO·Fe2O3·Cr2O3·MnO2·V2O5/HZS catalyst According to this technology, it is possible to obtain acetone of high purity, i.e. not less than 99.5%.
Keywords: acetone, isopropylbenzene, acetylene, Kume method, isopropanol, isopril, rectification, acrylnitrocellulose.